2013
DOI: 10.1002/hep.26157
|View full text |Cite
|
Sign up to set email alerts
|

Antimitochondrial antibody heterogeneity and the xenobiotic etiology of primary biliary cirrhosis

Abstract: Antimitochondrial antibodies (AMA) directed against the lipoyl domain of the E2 subunit of pyruvate dehydrogenase (PDC-E2) are detected in 95% of patients with PBC and are present before onset of clinical disease. The recent demonstration that AMA recognize xenobiotic modified PDC-E2 with higher titers than native PDC-E2, raises the possibility that the earliest events involved in loss of tolerance are related to xenobiotic modification. We hypothesized that reactivity to such xenobiotics would be predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 54 publications
4
57
0
1
Order By: Relevance
“…PBC exhibits several features characteristic of an autoimmune disease including the presence of the hallmark AMAs directed against the PDC-E2, autoreactive T cells in portal tracts and the specific immune targeting of cholangiocytes [45][46][47][48]. Thus PBC is an autoimmune disease and immunosuppressive agents, including corticosteroids, azathioprine, cyclosporin and methotrexate, should theoretically be successful to treat PBC; however, a clear benefit has not been demonstrated to date [4].…”
Section: T Cells But Not Cd4mentioning
confidence: 99%
“…PBC exhibits several features characteristic of an autoimmune disease including the presence of the hallmark AMAs directed against the PDC-E2, autoreactive T cells in portal tracts and the specific immune targeting of cholangiocytes [45][46][47][48]. Thus PBC is an autoimmune disease and immunosuppressive agents, including corticosteroids, azathioprine, cyclosporin and methotrexate, should theoretically be successful to treat PBC; however, a clear benefit has not been demonstrated to date [4].…”
Section: T Cells But Not Cd4mentioning
confidence: 99%
“…Compared to other biosimilar therapeutics, mAb and antibody-derivative biosimilars guidance has experienced delays. 6 The main reason is that antibody-derivatives are glycoproteins, which are large, complicated and heterogeneous proteins with the complex post-translational modifications (PTMs). Researchers have shown that regulatory approval of biosimilars of mAb and antibody-derivative is subjected to specific, science-based guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Some bacteria such as Escherichia coli have been proposed to cross-react with mitochondrial proteins, and this may explain why recurrent urinary infections are more commonly seen in PBC patients than in healthy controls [17] . Furthermore, the role of xenobiotics in PBC is thought to be important; the lipoyl domain of the immunodominant E2 component of pyruvate dehydrogenase (PDC-E2) can be replaced by a chemical xenobiotic mimic, which experimentally can be shown to be sufficient to break immunological self-tolerance [18] . Potential xenobiotics are speculated to be found in substances patients are commonly exposed to, including nail varnish, hair dye and cleaning chemicals [16] .…”
Section: Environmentmentioning
confidence: 99%